TINJAUAN YURIDIS TANGGUNG JAWAB LIKUIDATOR DALAM PEMBERESAN HARTA PERSEROAN YANG DIBUBARKAN - ANGELINE ANGELINE (PREMISE LAW JURNAL, 2017)
Liquidation of a corporation begins with the issuance of RUPS provision, followed by arrangement. A company arrangement is an action in the process of company liquidation in order to document and to sell or liquidate the company’s assets by distributing them to the persons entitled to them such as creditors and shareholders. In the process of liquidation, one or more liquidators are appointed to make the arrangement; but in practice, the process of arrangement is usually ignored by the owner of the company so that liquidation is not carried out of it is not completed. Therefore, it is necessary to analyze the responsibility of liquidator in the process of arranging the assets of liquidated corporation. Keywords: Responsibility, Liquidator, Liquidation of a Corporation, Liquidation